Study of Sambiloto Andrographis paniculate Ness. Extract as an Eco-Friendly Biocontrol on Weed Seed Germination and Growth - Madusari, Sylvia; Marzuki, Slamet; Yuliyanto, Yuliyanto (Journal of Applied Agricultural Science and Technology, 2023)
The use of synthetic herbicides causes many problems, including pollution, a decrease in soil organic content, and weed resistance to specific herbicides. Plants provide a source of novel phytotoxic compounds that can be evaluated in the search for efficient and ecologically safe herbicides. This research aimed to examine the allelochemical bioherbicidal activity of sambiloto (Andrographis paniculate Ness) leaf extract (SLE) to suppress weed seed germination and growth. The experiment was designed to investigate the effect of the SLE as a potent weed seed germination inhibitor and retard weed growth. In this experiment, a non-factorial randomized block design was used, with treatments SLE0 (0% Extract), SLE1 (Extract 0.1%), SLE2 (Extract 0.5%), SLE3 (Extract 1.0%), and SLE4 (Extract 1.5%). The result showed that weed height and biomass were significantly reduced after the extract was applied. The plant-based extracts contained 0.1114% flavonoids and 0.1628% tannins. The findings suggest that this sambiloto herbaceous extract has a promising future in modern plant protection as bioherbicide to suppress germination and weed growth. Therefore, the application of these bio-products could be beneficial for sustainable agricultural practices.